A security Assessment of Distribution Network CPS Based on Association Matrix Modeling Analysis. Issue 1 (May 2020) - Yang, Zhou; Zhou, Xia; Ni, Ming; Li, Manli; Lin, Husheng
Abstract: The addition of the information system has improved the operation of the distribution network CPS, but it also brings certain risks and impacts to the safety of the distribution network CPS operation. Therefore, the distribution network CPS security assessment needs to consider the impact of information systems. This paper proposes a security Assessment of Distribution Network CPS Based on Association Matrix Modeling Analysis. The research framework of information physical fault impact is proposed, and the correlation and impact of information physical failures are analyzed. The CPS model of distribution network based on association matrix is established, and the safety evaluation index and evaluation method are proposed. Case study shows the rationality and effectiveness of the proposed method.